NATURE OF THE DISTINCTION BETWEEN INTERNATIONAL HUMANITARIAN LAW AND INTERNATIONAL HUMAN RIGHTS LAW AS BRANCHES OF INTERNATIONAL LAW - Kremena RAYANOVA (Challenges of the Knowledge Society)
Despite the fact that there is a trend in understanding international humanitarian law and international human rights law as two separated branches of international law, discussions about these two concepts and their relationship continues. Rather than looking for which approach is correct, we should analyse what implications these discussions have in both theoretical and applied terms. To achieve that it is necessary to ascertain what is the nature and, consequently, what are the implications of identifying international humanitarian law and international human rights law as branches of international law, as well as the attributing specific norms to a particular branch.